KEPEMIMPINAN KIAI DALAM IDEOLOGISASI PEMIKIRAN SANTRI DI PESANTREN-PESANTREN SALAFIYAH MLANGI YOGYAKARTA - Zaenal Arifin (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
This research discusses about kyai’s leadership within santri’s ideological thought in Pesantren Salafiyah, Mlangi, Yogyakarta. There are more than 16 Pesantren Salafiyah in Mlangi, However, this qualitative research covers only five of them taken as purposive sampling. Data collection was conducted through in depth interview, observation, and documentation. The result shows that (1) The Kyai’s leadership is categorized under Weber’s theory of domination namely traditional, charismatic and rational, (2) Ahlussunah Waljamaah (Aswaja) an-Nahdliyah was held as the community’s ideology which is taught to santri by means of teaching Aswaja an-Nahdliyah classical books, strengthening alumnae allegiance, fostering Pesantren Salafiyah traditions, conducting Bahtsul Masa’il and Tafaqquh fiddin, regenerating young constituent by joining Nahdhatul Ulama membership, as well as by studying cross-Islamic school ofthought (ideology), and (3) the implications of this type of leadership on santri’s thought are fanatical attitude in following kyai’s religious thought (affected by traditional and charismatic leadership), non-dichotomical viewpoint on science and religion, and broader horizon on Islamic knowledge by studying contemporary Islamic books (affected by rational leadership)